2022
DOI: 10.1097/nne.0000000000001154
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to Success in Undergraduate Nursing Education Among Minority Students

Abstract: Increasing diversity in the nursing workforce has been cited as key to decreasing long-standing health disparities in the United States. [1][2][3] Yet, Black, Hispanic/ Latinx, Native American, and Asian American nurses remain inadequately represented in the health care workforce. 4 Most recent data from the 2018 National Sample Survey of Registered Nurses (RNs) show that White, non-Hispanic RNs accounted for 73.3% of the RN workforce, followed by Hispanic/Latinx (10.2%), Black non-Hispanic/Latinx (7.8%), Asia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 32 publications
(227 reference statements)
0
21
0
Order By: Relevance
“…We argue that the preference for the baccalaureate degree is a contemporary structure that maintains Eurocentric worldviews in nursing and perpetuates structural racism, both of which pose barriers for Black applicants pursuing a baccalaureate degree in nursing (Osakwe et al, 2022). Community colleges typically have a more diverse population of non-traditional students (characterized as financially independent and supporting dependents, lacking a high school diploma, and/or not entering college immediately after completing high school) (Petges & Sabio, 2020).…”
Section: Contemporary Eurocentrism In Nursingmentioning
confidence: 99%
See 2 more Smart Citations
“…We argue that the preference for the baccalaureate degree is a contemporary structure that maintains Eurocentric worldviews in nursing and perpetuates structural racism, both of which pose barriers for Black applicants pursuing a baccalaureate degree in nursing (Osakwe et al, 2022). Community colleges typically have a more diverse population of non-traditional students (characterized as financially independent and supporting dependents, lacking a high school diploma, and/or not entering college immediately after completing high school) (Petges & Sabio, 2020).…”
Section: Contemporary Eurocentrism In Nursingmentioning
confidence: 99%
“…Community colleges typically have a more diverse population of non-traditional students (characterized as financially independent and supporting dependents, lacking a high school diploma, and/or not entering college immediately after completing high school) (Petges & Sabio, 2020). A recent systematic review of 14 cross-sectional and qualitative studies from 1999 to 2020 identified barriers to racial and ethnic minority nursing students' success in undergraduate nursing programs; these barriers included personal-level, school environment, home environment, and financial barriers (Osakwe et al, 2022). Personal-level barriers to success included fear, anxiety, a reduced sense of belonging, and/ or perceived marginalization.…”
Section: Contemporary Eurocentrism In Nursingmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor interactions with fellow students also cause minority students to feel less supported (Osakwe, et al, 2022; Williams et al, 2018). More specifically, not having a supportive mentor or lack of school-provided mentorship programs was a common theme in several studies (Metzger, Taggart, et al, 2020; Osakwe, et al, 2022; Williams, et al, 2018). Student success has been tied to environments that promote inclusivity and to those in which minority faculty and students are adequately represented among the population (Metzger, Dowling, et al, 2020; Williams, et al, 2018).…”
Section: School and Campus Environmentmentioning
confidence: 99%
“…Many underrepresented minority (URM) students may be more at risk when enter nursing programs due to inequalities associated with secondary education in economically disadvantaged communities. 9,10 Studies also have shown that URM students face other obstacles or barriers (financial, work issues, childcare, family responsibilities, family crisis, lack of support, and transportation issues) outside of academics that contribute to higher rates of attrition among this group. 11,12 A recent review by Osakwe et al 9 revealed barriers or obstacles to be social isolation, caregiving demands, lack of mentorship, and inadequate financial resources.…”
Section: Review Of the Literaturementioning
confidence: 99%